Rational numbers operations: What (mis)understandings do children demonstrate? - Graça, Sofia (2019)
This qualitative and interpretative study aims to identify grade 5 students’ knowledge of rational number operations in order to ascertain their rational number sense and operation sense before and after a teaching experiment. Data was gathered using two tests and four individual semi-structured interviews. The results show that, in the pre-test, children performed rational number operations based on their whole number knowledge. In the post-test, after the teaching experiment, they showed conceptual understanding of the operations, demonstrating rational number sense and operation sense.